لمحة موجزة عن أساليب واستراتيجيات التدريس في القرآن الكريم: A Brief Overview of Teaching Methods and Strategies in The Holy Quran - Garba, Ahmad (Al-Wasil, 2025)
Among the guidance of the Holy Quran to mankind is the principles of learning, Quran was revealed primarily for the purpose of guiding, directing, and teaching man. Therefore, it was natural for the Holy Quran to include a lot of information about man. it contains information about the creation of man and the nature of his composition of matter and spirit, and the psychological conflict that arises from that, and the different physiological and psychological motivations that direct his behavior, as well as the various emotions that he feels and that affect his life, and the means by which man acquires knowledge, whether through sensory or mental perception or through inspiration and true vision. Not only that, the holy Qur'an also contains information about the growth and developmental stages of a man, equally about learning and its principles, personality and its different types and characteristics, human evaluation and psychological treatment and other information about human physiological life. we have learned from the Holy Quran many methods of teaching and learning that aim to prepare the learner to be a good role model by embodying good behavior in dealings, consequently, learners vary in their mental abilities, readiness, and intelligence the Holy Quran has drawn attention to the necessity of taking into account the characteristics of each stage of growth when giving educational and pedagogical doses to individuals. On this basis, this paper aims to shed light on some of the principles and teaching methods mentioned in the Holy Quran, and the extent of its impact in responding to students' desire for education and learning. descriptive research design was used to obtain valuable information related to the topic. The research results also concluded that the Holy Quran has an attractive and distinctive methods in teaching and modifying the learner's behavior to a desired form through a gradual processes.